MARKERS OF ARTERIAL STIFFNESS AND SUBCLINICAL VASCULAR DAMAGES IN OBESE CHILDREN. (June 2018) - Bonafini, S.; Tagetti, A.; Giontella, A.; Minuz, P.; Maffeis, C.; Antoniazzi, F.; Fava, C.
Abstract : Objective: We aimed at investigating the influence of weight excess and traditional cardiovascular risk factors on vascular structure and function in a sample of obese children. Design and method: Overweight or obese children (BMI > 90th percentile for sex and age) included in this observational study underwent office and ambulatory BP measurements (ABPM) and the assessment of carotid intima-media thickness (cIMT), endothelial function by the Flow Mediated Dilation (FMD) technique, carotid distensibility (cDC) by ultrasounds and stiffness index (SI) by digital photopletismography. Results: Sixty-six obese and 4 overweight children were enrolled (age 11.5 ± 2.4 years; female n: 30). Carotid IMT directly correlated with 24h- and nighttime SBP; cDC showed inverse correlations with BMI and waist circumference and 24h-BP. Unexpectedly, SI resulted inversely related with several indexes of weight excess. Most of these correlations remained significant after adjustment for age, sex, BMI and BP. In a replication set of 40 obese children SI, but not Pulse Wave Velocity (PWV), was still inversely associated with BMI. Conclusions: These data suggest that arterial structure and elasticity are negatively affected by weight excess and BP levels, even in childhood. Surprisingly, SI might not be a reliable marker of vascular stiffness in obese children, because this measure is probably confounded by other factors including vasodilation.